EFEKTIVITAS MOBILE BANKING DALAM MENINGKATKAN INKLUSI KEUANGAN MASYARAKAT - Achmarul Fajar; Moh Dimas Dwi Prima; Moh. Fajar Firmansyah; Fahrul Rosi (PT. Hasba Edukasi Mandiri, 2026)
The rapid development of digital technology has transformed the way people access financial services. Mobile banking has emerged as an innovative solution that enables users to conduct financial transactions conveniently, quickly, and efficiently without visiting physical bank branches. This study aims to analyze the effectiveness of mobile banking in enhancing financial inclusion and identify the factors that support or hinder its adoption. The research employs a qualitative descriptive approach through a literature review of scientific journals, international reports, and official documents published between 2021 and 2025. The findings indicate that mobile banking significantly contributes to expanding access to financial services, particularly among rural communities, low-income groups, and micro-enterprise owners. Ease of access, cost efficiency, and the availability of services around the clock are the main drivers of increased financial inclusion. Nevertheless, the effectiveness of mobile banking is constrained by several challenges, including limited digital financial literacy, technological infrastructure disparities, cybersecurity risks, and unequal internet access. Therefore, collaboration among governments, financial institutions, technology providers, and society is essential to improve digital literacy, expand technological infrastructure, and strengthen digital transaction security. With appropriate policy support, mobile banking has substantial potential to become a strategic instrument for achieving a more inclusive and sustainable financial system.